2018
DOI: 10.1002/cche.10099
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci regulate the concentrations of steryl ferulates in brown rice

Abstract: Background and objectives: γ-Oryzanol and its major components, 24-methylenecycloartanyl ferulate and cycloartenyl ferulate, which are distributed in the rice bran layer, exert biomedical effects. The objective of the present study was to detect QTLs regulating the concentrations of 24-methylenecycloartanyl ferulate and cycloartenyl ferulate by using the reciprocal CSSLs derived from a cross between an indica-type cultivar Takanari and a japonica-type cultivar Koshihikari, having low and high concentrations, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 20 publications
6
24
3
Order By: Relevance
“…These results corroborate the findings of Kato et al (2017) who compared the GO concentration between Indica and Japonica varieties, reporting there are quantitative trait loci (QTL's) responsible for GO concentrations; the authors also referred a significantly higher GO concentration in Japonica types compared with Indica types (Kato et al, 2017). Nakano et al (2018) studied the genetic differences between Japonica and Indica types regarding the major compounds of GO (24-MCAF, and CAF), reporting there are alleles from Japonica type varieties that can be used to improve GO concentration on Indica types. Those findings can contribute to the genetic improvement of rice regarding its GO content.…”
Section: Rice Bran Go Contentsupporting
confidence: 88%
See 2 more Smart Citations
“…These results corroborate the findings of Kato et al (2017) who compared the GO concentration between Indica and Japonica varieties, reporting there are quantitative trait loci (QTL's) responsible for GO concentrations; the authors also referred a significantly higher GO concentration in Japonica types compared with Indica types (Kato et al, 2017). Nakano et al (2018) studied the genetic differences between Japonica and Indica types regarding the major compounds of GO (24-MCAF, and CAF), reporting there are alleles from Japonica type varieties that can be used to improve GO concentration on Indica types. Those findings can contribute to the genetic improvement of rice regarding its GO content.…”
Section: Rice Bran Go Contentsupporting
confidence: 88%
“…Stress conditions as temperature or drought may also be a factor affecting the GO content, and 4.5 o C temperature increase resulted in higher GO values, mainly on the 24MCAF fraction (Britz et al, 2007); the sterol content and steryl ester fractions of two cultivars seemed to increase when subjected to water stress through 3, 6, 9 and 12 days (Kumar and Krishna, 2015). Genetics also plays an important role regarding the GO content, as some specific alleles may be responsible for GO concentration (Kato et al, 2017;Nakano et al, 2018). Nakano et al (2018) studied the progenies from the cross of indica and japonica germplasm, by analysing 80 lines concluded that alleles from the japonica type may improve GO, 24MCAF and CAF concentrations in indica types, while indica type alleles may be used to improve CAF concentrations in japonica types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are apparent variations in the contents of these compounds among rice cultivars (Bergman & Xu, 2003;Heineman et al, 2008;Huang & Ng, 2011;Kato et al, 2017;Ng et al, 2013). Several quantitative trait loci have been identified for the contents of gOZ (Kato et al, 2017;Nakano et al, 2018) and vitamin E derivatives (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 More recently, we have identified QTLs for the concentration of γ-oryzanol using the CSSLs. 14…”
Section: Introductionmentioning
confidence: 99%